Designing brand identity a comprehensive guide to the world of brands and branding - Wheeler, Alina; Meyerson, Rob (Hoboken, New Jersey John Wiley & Sons, 2024)
From research to brand strategy to design execution, launch and governance, Designing Brand identity is a compendium of tools for branding success and best practices for inspiration. The best-selling book demystifies branding, explains branding fundamentals, and gives practitioners a roadmap to create sustainable and successful brands. This revised and updated 6th edition will preserve the basic structure of the book (fundamentals, process, and strategy). With each topic covered in a single spread, the book continues to celebrate great design and strategy--while adding new thinking, new case studies, and more future-facing, global perspectives. Designing Brand Identity, 6th Edition, has been revised and updated throughout to address the challenges faced by branding professionals today. It's harder than ever to be the brand of choice--in many markets, technology has lowered the barriers to entry, increasing competition. The need for fresh content is relentless. Everything is digital, and rebranding projects that previously took a year are now finished in three months. Decisions that used to be straightforward are now complicated by the pandemic, political polarization, rapid advances in technology, and other social and cultural changes"--
Keywords: Brand name products; Branding (Marketing); Advertising -- Brand name products; Trademarks -- Design